2019
DOI: 10.1148/ryct.2019190050
|View full text |Cite
|
Sign up to set email alerts
|

Coronary CT Angiography-derived Fractional Flow Reserve Testing in Patients with Stable Coronary Artery Disease: Recommendations on Interpretation and Reporting

Abstract: Noninvasive fractional flow reserve derived from coronary CT angiography (FFR CT ) is increasingly used in patients with coronary artery disease as a gatekeeper to the catheterization laboratory. While there is emerging evidence of the clinical benefit of FFR CT in patients with moderate coronary disease as determined with coronary CT angiography, there has been less focus on interpretation, reporting, and integration of FFR CT results into routine clinical practice. Because FFR CT analysis provides a plethora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 43 publications
3
65
0
4
Order By: Relevance
“…Using the FFR CT algorithm, the most widespread standard developed by HeartFlow Inc. (Redwood City, Calif), recent studies have shown that 35–44% of patients with stable coronary artery disease and lowest FFR CT as positive were reclassified as negative when the FFR CT measurement point was 1-to-2 cm distal to a stenosis [17] , [18] . As a recent study also highlighted that the diagnostic performance of FFR ct measured at 1-to-2 cm distal to the stenosis was significantly higher than that of far-distal segments [19] , it is now recommended to measure FFR CT 1-to-2 cm distal to the end of a focal stenosis [20] . This is the first study, using the CT-FFR algorithm, which demonstrated the diagnostic performance of CT-FFR was significantly better when measured at 1-to-2 cm distal to a target stenosis than measured at the vessel terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Using the FFR CT algorithm, the most widespread standard developed by HeartFlow Inc. (Redwood City, Calif), recent studies have shown that 35–44% of patients with stable coronary artery disease and lowest FFR CT as positive were reclassified as negative when the FFR CT measurement point was 1-to-2 cm distal to a stenosis [17] , [18] . As a recent study also highlighted that the diagnostic performance of FFR ct measured at 1-to-2 cm distal to the stenosis was significantly higher than that of far-distal segments [19] , it is now recommended to measure FFR CT 1-to-2 cm distal to the end of a focal stenosis [20] . This is the first study, using the CT-FFR algorithm, which demonstrated the diagnostic performance of CT-FFR was significantly better when measured at 1-to-2 cm distal to a target stenosis than measured at the vessel terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Tools such as Sim-Vascular have been key in research on individualized medicine, surgical planning and medical device design [Updegrove et al, 2017]. Recently, CTA derived fractional flow reserve became the first and only simulation-based technology approved by the United States Food and Drug Administration for CAD diagnosis; this method is being implemented by HeartFlow Inc, in Redwood City, California [Nørgaard et al, 2019]. Other noninvasive methods based on machine learning and reduced order models have also been increasing in popularity [Douglas et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…A d-FFR CT -value ⩽0.75 was indicative of impaired flow. 26,27 Follow-up Electronic patient journals were used to register major adverse outcomes (all-cause mortality, myocardial infarction and stroke) at follow-up, 4 to 6 years after the initial coronary CTA.…”
Section: Ffr Ctmentioning
confidence: 99%